Precipitation variability, trends and regions in Poland: Temporal and spatial distribution in the years 1951–2018 - Kalbarczyk, Robert; Kalbarczyk, Eliza (Acta geographica Slovenica, 2021)
The goals of this work were to assess differences in precipitation totals (Pr) in Poland in both time and space and to distinguish regions based on precipitation variability in the years 1951–2018. To assess precipitation conditions, the study used statistical and spatial analyses implemented in ArcGIS Desktop and STATISTICA software. The largest number of significant, positive correlations describing the linear Pr trend were found for March. The lowest monthly Pr, which represents only approximately 6% of the multiyear precipitation totals, was recorded in October 1951; the highest monthly Pr, which represents as much as approximately 355% of the multi-year precipitation totals, was recorded in October 1974. The study distinguished three precipitation regions of Poland.